Agrivoltaics in Japan: A Review of Current Practices, Challenges, and Future Directions - Aditama, Kevin Muhammad Tegar; Al Wafi, Ahmad Zein (SHM Publisher, 2025)
This review examines agrivoltaics in Japan integrating solar photovoltaic (PV) systems with agricultural production as a dual-use land strategy to address constrained arable land, decarbonization goals, and energy security. Using a thematic synthesis of published studies and documented Japanese cases, the paper maps current deployment practices, reported agronomic and energy outcomes, and the main constraints shaping adoption. The literature indicates that well-designed agrivoltaic configurations can maintain crop production while adding renewable electricity generation, with outcomes strongly influenced by site conditions, crop type, shading design, and farm management. Evidence also points to potential co-benefits such as reduced heat stress and improved microclimate stability, but trade-offs may emerge for light-sensitive crops or under suboptimal PV spacing and height. Key barriers in Japan include high upfront investment, complex permitting and compliance requirements, and concerns over land-use integrity and long-term agricultural continuity. Future research should prioritize longitudinal field data on crop yield and quality, soil and water dynamics, and ecosystem effects, alongside standardized performance metrics and policy/financing mechanisms that align farmer incentives with grid and climate objectives.